DIMENSI KUALITAS DAN HARGA SEBAGAI FAKTOR PENENTU KEPUASAN DAN LOYALITAS KONSUMEN - Untung Sriwidodo, Ernawati & (Universitas Slamet Riyadi, 2012)
ABSTRACT The relatively service-driven restaurant industry is becoming more important in generating income for many countries and hence the service performance of the restaurants must be well understood and managed. The key determinants for restaurant service quality need to be identified, especially for the important segment such as youth consumers. Therefore, this study aims to explore the importance of physical environment quality, human service, food quality and price from the youth consumer’s perspective. This study using 100 youth consumers in Waroeng